Electrochemical determination of hydrazine by using MoS2 nanostructure modified gold electrode - Rana, Dharmender Singh; Thakur, Nagesh; Thakur, Sourbh; Singh, Dilbag (Nanofabrication, 2022)
In this paper, MoS2 nanostructure was synthesized by using ammonium molybdate and thiourea as precursors through annealing in a tube furnace. The nanostructure was characterized for morphological, structural and elemental composition by using a field emission scanning electron microscope (FESEM), powder X-ray diffraction and energy-dispersive X-ray spectroscopy (EDS). The as-synthesized nanostructure was then immobilized on the gold electrode (working electrode) for the electrochemical detection of hydrazine. Cyclic voltammogram shows an intense peak at 22 µA, which proved the high electrocatalytic ability of the sensor. The strong electrocatalytic activity regarding the oxidation of hydrazine is ascribed to good electron transfer ability and high surface area of the nanoparticles. Further, the chronoamperometric study was conducted to estimate the sensitivity and the detection limit of the sensor. The sensor exhibited a detection limit and sensitivity of 196 nM and 5.71 µA/µM cm2 respectively. Promising results such as high electrical conductivity, lower detection limit and high sensitivity of the as-synthesized MoS2 nanostructure have proved its potential towards the electrochemical detection of hydrazine.